2012
DOI: 10.1016/j.nima.2011.11.075
|View full text |Cite
|
Sign up to set email alerts
|

Tests of modulated intensity small angle scattering in time of flight mode

Abstract: We report results of tests of the MISANS technique at the CG-1D beamline at High Flux Isotope Reactor (HFIR), Oak Ridge National Laboratory (ORNL). A chopper at 40 Hz simulated a pulsed neutron source at the beamline. A compact turn-key MISANS module operating with the pulsed beam was installed and a well characterised MnSi sample was tested. The feasibility of application of high magnetic fields at the sample position was also explored. These tests demonstrate the great potential of this technique, in particu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Another purpose of this experiment was to compare our MI-SANS measurement on a pulsed source with measurements performed at a continuous source. The implementation of MI-SANS geometry has been proposed on a pulsed source (Bleuel et al, 2005(Bleuel et al, , 2006 and demonstrated using a reactor source with a chopper on a skyrmion system (Brandl et al, 2012). The RESEDA beamline at the FRM-II neutron source (at the MLZ, Munich, Germany) has performed many MI-SANS experiments at constant wavelength .…”
Section: Discussionmentioning
confidence: 99%
“…Another purpose of this experiment was to compare our MI-SANS measurement on a pulsed source with measurements performed at a continuous source. The implementation of MI-SANS geometry has been proposed on a pulsed source (Bleuel et al, 2005(Bleuel et al, , 2006 and demonstrated using a reactor source with a chopper on a skyrmion system (Brandl et al, 2012). The RESEDA beamline at the FRM-II neutron source (at the MLZ, Munich, Germany) has performed many MI-SANS experiments at constant wavelength .…”
Section: Discussionmentioning
confidence: 99%
“…The operation of a MIEZE-1 spectrometer using a pulsed neutron beam has already been tested recently [40] and the necessary adaption in the sweeping of the amplitude of the RFfields has already been developed. It is planned to base the data evaluation on the existing ILL code library for NSE instruments as used at the ILL and the FRM II.…”
Section: Mieze-1mentioning
confidence: 99%
“…The TOF-MIEZE technique has been tested as a means of efficiently measuring I(Q, τ) using pulsed neutron beams, with frequencies from a few kHz up to 50 kHz reported in the literature [16][17][18][19]. The method requires a resonance spin flipper (RSF) that works for pulsed white beams, which can be achieved using a time-modulated RF current [20].…”
Section: Introductionmentioning
confidence: 99%